Immunity to stripe rust in wheat: A case study of a hypersensitive-response (HR)- independent resistance to Puccinia striiformis f. sp. tritici in Avocet-Yr15. (13th December 2021) - Seifi, Hamed (Soren); Serajazari, Mitra; Kaviani, Mina; Pauls, Peter; Booker, Helen; Navabi, Alireza
Abstract: Stripe (yellow) rust, caused by the biotrophic fungal pathogen Puccinia striiformis f. sp. tritici (Pst), is emerging as a serious threat to wheat ( Triticum aestivum L.) production in many regions of North America. Genetic resistance to stripe rust is typically conditioned by the products of resistance genes that detect pathogen-associated molecular patterns and initiate a cascade of signalling events, culminating in the generation of reactive oxygen species (ROS) and a hypersensitive response (HR) that eventually suppress the pathogen. Complete resistance with no symptoms (immunity response) has also been observed, but less frequently, in certain Pst-wheat interactions. However, such HR-independent resistance responses to Pst have not been well studied. Here we report that the Pst-resistant near isogenic line Avocet- Yr15 (carrying the Yr15 resistance gene) exhibited an immunity response to an isolate of Pst collected in Elora, Ontario, while the Avocet-S line (lacking Yr15 ) was highly susceptible to the same isolate. In particular, histochemical assays of defence-associated ROS generation and HR were negative during the early stages of the interaction between Pst and the resistant Avocet- Yr15 . Microscopic analysis indicated that the pathogen was not able to penetrate the stomata of Avocet- Yr15 . Moreover, RNA-sequencing of the immunity response of Avocet- Yr15 to Pst highlighted the activation of a global anti-oxidative-stress response consisting of genes involved in the maintenance of cell viability, redox homoeostasis and photosynthesis. These results provide insights into the molecular mechanisms controlling the immunity response to stripe rust of wheat.